Integrated management of fusarium wilt of gladiolus (Bangladesh Journal of Agricultural Research, 2018)
Integrated management of Fusarium wilt of gladiolus was studied at Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during 2011-2013 following RCB design with four replications. Seven treatment such as (1) Corm treated with Bavistin @ 0.1% for 15 minutes, (2) Corm treated with hot water @ 54oc for 5 minutes, (3) Corm treated with hot water @ 52oc for 10 minutes, (4) Poultry refuse @ 5t/ha, (5) Mustard oil cake @ 600 kg/ha, (6) Bio-pesticide @ 64kg/ha, (7) Bavistin @ 0.1% as soil drenching were evaluated in nine different combinations against the Fusarium wilt of gladiolus (Fusarium oxysporum f. sp. gladioli) under naturally infested field condition. Corm treated with Bavistin (0.1%) for 15 minutes + Poultry refuse @ 5t/ha in soil application 25 days before corm sowing + Bavistin @ 0.1% as soil drenching at 45 days after corm sowing gave best integrated management option for reducing Fusarium wilt of gladiolus and thereby resulting maximum germination, spike length, rachis length, florets spike-1, flower sticks, corm and comel yield. Besides, integration of Bavistin (0.1%) as corm treatment for 15 minutes + Mustard oil cake @ 600 kg/ha in soil application 25 days before corm sowing + Bavistin (0.1%) as soil drenching at 45 days after corm sowing was also better option for combating Fusarium wilt of gladiolus. The alternate option was integration of Bavistin (0.1%) as corm treatment for 15 minutes + Bio-pesticide in soil application 7 days before corm sowing + Bavistin (0.1%) as soil drenching at 45 days after corm sowing was effective against the disease incidence as well as better spike length, rachis length, florets spike-1, flower sticks, corm and cormel yield.Bangladesh J. Agril. Res. 43(1): 13-23, March 2018